2017
DOI: 10.1016/j.neuropsychologia.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Switching direction affects switching costs: Behavioral, ERP and time-frequency analyses of intra-sentential codeswitching

Abstract: Bilinguals have the unique ability to produce utterances that switch between languages. Most language switching research has focused on isolated, unrelated items, which emphasizes separation of the languages. Fewer studies examined the cognitive and neural mechanisms of switching languages in natural discourse. The present study examined the effect of codeswitching direction on the comprehension of intra-sentential codeswitching in Spanish-English bilinguals, using self-paced reading behavioral measurements (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
120
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 78 publications
13
120
5
Order By: Relevance
“…Initial switch costs occurred for both participants reading in their L2 (Experiment 1) and those reading in their L1 (Experiment 2). This finding is in line with many previous studies demonstrating that language switching is associated with a measurable processing cost due to demands associated with suppressing the non-target language or reactivating the target language in the face of persistent activation from the previous language (Bobb & Wodniecka, 2013;Bultena et al, 2015a;2015b;Declerck & Philipp, 2015;Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Philipp, Gade, & Koch, 2007;Litcofsky & Van Hell, 2017;Meuter & Allport, 1999;Verhoef, Roelofs, & Chwilla, 2009;Wang, 2009). In our data, switch costs continued to influence downstream processing at a later point in the sentence, particularly in relation to the magnitude of cross-language activation measured by homograph effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Initial switch costs occurred for both participants reading in their L2 (Experiment 1) and those reading in their L1 (Experiment 2). This finding is in line with many previous studies demonstrating that language switching is associated with a measurable processing cost due to demands associated with suppressing the non-target language or reactivating the target language in the face of persistent activation from the previous language (Bobb & Wodniecka, 2013;Bultena et al, 2015a;2015b;Declerck & Philipp, 2015;Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Philipp, Gade, & Koch, 2007;Litcofsky & Van Hell, 2017;Meuter & Allport, 1999;Verhoef, Roelofs, & Chwilla, 2009;Wang, 2009). In our data, switch costs continued to influence downstream processing at a later point in the sentence, particularly in relation to the magnitude of cross-language activation measured by homograph effects.…”
Section: Discussionsupporting
confidence: 91%
“…A vast body of evidence shows that the exogenous requirement to switch languages during word naming or when reading has consequences for language processing, notably in the form of language switching costs (e.g., Altarriba, Kroll, Sholl, & Rayner, 1996;Bultena, Dijkstra, & Van Hell, 2015a;2015b;Costa & Santesteban, 2006;Declerck & Philipp, 2015;Gollan & Ferreira, 2009;Litcofsky & Van Hell, 2017;Meuter & Allport, 1999;Wang, 2015; for a review, see Bobb & Wodniecka, 2013). Switch costs in language production, particularly asymmetric switch costs that are larger into the dominant language, are the hallmark evidence for control accounts and are frequently interpreted as evidence for the inhibition of a previously activated non-target language, typically the L1 (e.g., Abutalebi & Green, 2008;Bobb & Wodniecka, 2013;Green, 1998;Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Meuter & Allport, 1999).…”
mentioning
confidence: 99%
“…Yet, the processing of code-switched speech remains understudied in comparison. Broadly speaking, much of the early work on code-switching indicates that, just like in task switching (Monsell 2003) and cued-language switching (Meuter and Allport 1999), integrating code-switches in realtime processing leads to greater switch costs relative to unilingual processing (Altarriba, Kroll, Sholl and Rayner 1996;Litcofsky and Van Hell 2017). Nevertheless, recent available literature has revealed that switch costs may be attenuated under certain social or linguistic contexts (Beatty-Martínez and Dussias 2017; Fricke, Kroll and Dussias 2016;Guzzardo Tamargo, Valdés Kroff and Dussias 2016;Valdés Kroff, Guzzardo Tamargo, and Dussias 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The current psycholinguistics studies of code-switching highlight three broad themes of study: (1) Its relationship to other switching phenomena such as cued language switching (e.g., Meuter and Allport 1999;Gollan and Ferreira 2009) and non-linguistic switching tasks (e.g., Monsell 2003); (2) Whether the integration of code-switching in production and comprehension leads to processing costs (e.g., Beatty-Martínez and Dussias 2017; Fernandez, Litcofsky, and Van Hell 2019;Litcofsky and Van Hell 2017); and (3) The cognitive and grammatical processes that help bilinguals rapidly integrate code-switched speech in production and comprehension (e.g., Adler, Valdés Kroff and Novick in press;Fricke et al 2016;Gullifer and Titone 2019;Guzzardo Tamargo et al 2016;Kootstra, Van Hell and Dijkstra 2012;Valdés Kroff, Dussias, Gerfen, Perrotti and Bajo 2017). These three themes are inter-related in that the natural parallel between general switching behavior and the robust switch costs reported from the cued language switching paradigm leads to the logical prediction that code-switching should similarly evince costly integration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation